The Eudemonic Wellbeing of Volunteers in a Public Health Emergency: COVID-19 in China - Tang, Juan; Li, Xiao-chen; Zhang, Xi (Frontiers in Psychology, 2022)
With improvements in the public’s awareness of volunteer opportunities, many more people participate in social work, especially during emergency events. Volunteers’ mental health has begun attracting more academic attention due to its increasing social significance. Drawing on the Theory of Planned Behaviour, a qualitative interview was constructed to identify important attitudes, subjective norms, and perceived control factors guiding people’s volunteering behaviours in an emergency context. Then, a sequential quantitative survey was implemented based on the results of the qualitative study to explore the impact of the aforementioned factors and job involvement on eudemonic well-being. The moderating role of empathy in these relationships was also investigated in this nested design. The results indicate that behavioural attitudes, perceived control and job involvement have significant positive effects on volunteers’ eudemonic well-being. A high perspective taking (cognitive empathy) of volunteers positively moderate the relationship between job involvement and eudemonic well-being. While high personal distress (affective empathy) buffers this relationship. The theoretical and practical implications of these findings are discussed in relation to emergency volunteer activities.